2014
DOI: 10.1586/1744666x.2014.904746
|View full text |Cite
|
Sign up to set email alerts
|

The current relevance and use of prednisone in rheumatoid arthritis

Abstract: Prednisone is an old and very valuable drug in clinical use for over 60 years by now. It is well known by physicians and widely used for different kinds of inflammatory states including rheumatoid arthritis (RA). Clinical trials during the last 20 years have changed its clinical use, particularly with regards to dosage. Today, rheumatologists are treating their patients much more likely over a long period of time using a low-dose scheme. The effectiveness and safety of this low-dose use is the objective of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 101 publications
0
28
0
Order By: Relevance
“…In this line it was shown that CD14 1 CD56 1 monocytes also expressing CD16 were more prone to express inflammatory cytokines, such as IL-1b and IL-23, and were expanded in conditions associated with inflammatory and autoimmune diseases. [39][40][41] Although this monocyte subset still need to be investigated in patients with BP, one can notice that IL-23 is overexpressed in the serum of patients with BP compared with expression in age-and sexmatched control subjects and is even increased in the serum of patients with BP who later experience a relapse. 6 Because CXCL10 increases its own production by monocytes in some patients with BP, this could further amplify MMP-9 production in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this line it was shown that CD14 1 CD56 1 monocytes also expressing CD16 were more prone to express inflammatory cytokines, such as IL-1b and IL-23, and were expanded in conditions associated with inflammatory and autoimmune diseases. [39][40][41] Although this monocyte subset still need to be investigated in patients with BP, one can notice that IL-23 is overexpressed in the serum of patients with BP compared with expression in age-and sexmatched control subjects and is even increased in the serum of patients with BP who later experience a relapse. 6 Because CXCL10 increases its own production by monocytes in some patients with BP, this could further amplify MMP-9 production in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with synthetic DMARDs, such as methotrexate, radiographic joint damage is reduced when used over a longer period (2–4 years), even after discontinuing IR prednisone. 35 Since MR prednisone is virtually the same drug with almost identical pharmacodynamics and just an envelope ensuring a delayed liberation, a similar effect could be concluded on the long run.…”
Section: Efficacymentioning
confidence: 97%
“… 34 Details on this topic and the (non)genomic effects of prednisone are extensively discussed elsewhere. 35 …”
Section: Pharmacology and Drug Developmentmentioning
confidence: 99%
“…Glucocorticoids have the ability to reduce signs and symptoms in inflammatory disorders; therefore, they are widely used to treat RA [53]. Prednisone is an important drug which is used to treat different kinds of inflammatory conditions including RA [54].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%